Influência do uso da terra em variáveis limnológicas no Rio Soturno, Rio Grande do Sul - Brasil - Alberti, Edison Antonio (2015)
The watershed of Soturno River is located in the center of the state of Rio Grande do Sul, and covers a total area of 987.18 km². The objectives of this research were the interpretation, analysis and the relation of land use and coverage, in different periods of the year, through limnological data. The methodology consists in the acquisition of land use data focused on two distinct phases of the agricultural calendar, that is, one in the period between harvests, which corresponds to winter, and the other in the period of growth and phenological development of the crops, which corresponds to summer. The OLI images (Operational Land Imager) of the Landsat-8 platform, composition RGB432, were used to identify the types of land use. The classes of land use that resulted were: agriculture, field, forest, water, urban areas and shadow. The limnological variables were: water temperature, air temperature, hydrogen potential, electric conductivity, total of solids in suspension, turbidity and water transparency. The limnological variables were measured in two different sample groups: the first period from June 15, 2014 to November 30, 2014, in this modality, weekly samples were collected, in a total of 25 collections in a single point; the second on November 14, in 12 sample points, and distributed throughout the whole watershed. In possession of these information, a database considering the land use variables on the perspective of human action on this space was organized and the limnological variables on the perspective of a system of longitudinal, open and continuous flow. Thereby, the influence and the correlation of different land uses on aquatic environments were evaluated and, if throughout the year, the phases of agricultural activity provided different responses on the quality of water. In the classification of satellite images, the classes of field and agriculture out stood. In the agricultural class, it is evident the reduction of 86.46% of planted area in the summer season when compared to winter. The class field showed the opposite behavior, that is, an increase of 234.15% of this area in winter season. The forest class out stands because it occupies an area of approximately 35% of the total of the watershed, with an emphasis on the edge of the Plateau. Among the limnological variables presented in the work, it should be pointed out the water transparency with a variation from 8 cm to 145 cm, the turbidity with a variation of 4.68 to 492.00 NTU (Nephelometric Turbidity Units), the TSS (Total Suspended Solids) ranged from 3.33 mg/L to 334.00 mg/L. It has been evident that the uses and land coverage on the area of study are mainly rural, drawing attention to soy and corn cultivation in the Highlands and rice in the Lowlands. Facing the results, the importance of this work lies on the acquisition of knowledge and the creation of data about how these water resources respond to anthropic action, knowing that these findings contribute to the maintenance of the quality of water of these watershed, as well as comprehending the processes the happen in these environments.